The relationship between perceptions of recovery and pain beliefs in occupational overuse syndrome : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University - Allison, Lucinda (Massey University, 2001)
Occupational Overuse Syndrome (OOS or RSI) is an umbrella term for a range of conditions characterised by pain and discomfort in the soft tissues and muscle weakness. Cognitive-behavioural theory suggests that the beliefs of people in pain can influence their functioning and research findings support a relationship between pain beliefs and levels of pain and functioning. However there has been little research into how beliefs influence recovery from the range of OOS conditions. The main goals of this study were to examine the relationship between pain beliefs and recovery and between pain and functioning. Sixty-four people with OOS completed questionnaires to determine their pain beliefs and levels of pain and functioning. Correlations provided little support for a relationship between beliefs and recovery but supported a relationship between pain and functioning. This study highlighted the limitations of the beliefs research and recommended that future research investigate the influence of the interaction of beliefs and treatment on recovery. It also highlighted the importance of distinguishing between the different types of OOS rather than treating them all as the same condition.
Keywords: Overuse injuries; Pain; Psychological aspects